Understanding employee contentment in the hospitality sector: An IPA approach to evaluate satisfaction and performance - Narti, Ni Ketut; Suryaniadi, Sagung Mas; Wijayati, Ni Luh Made (Journal of Commerce, Management, and Tourism Studies, 2025)
This study aims to assess the level of employee job satisfaction at CUC Hotel and identify areas for improvement using the Importance Performance Analysis (IPA) method. Job satisfaction plays a critical role in enhancing employee productivity and retention, particularly in the hospitality industry, where human resources are vital to operational success. A quantitative descriptive approach was employed, with data collected through a structured questionnaire. The study's population comprises all employees at CUC Hotel, and a sample of 67 respondents was selected using probability sampling techniques. Data analysis was conducted using descriptive statistics to calculate average scores for each indicator, followed by IPA to map satisfaction attributes into quadrants based on their importance and performance. The IPA results indicate that four key attributes are situated in Quadrant I (high importance, low performance) of the Cartesian diagram: promotion opportunities, co-worker relationships, and supervisor relationships. These findings suggest that while these attributes are deemed highly important by employees, their current performance is inadequate and requires managerial attention. The overall conformity level of 85.56% suggests that employee job satisfaction at CUC Hotel is generally favorable. The study recommends that management prioritize improvement efforts on attributes within Quadrant I to ensure sustained and effective enhancement of employee satisfaction.